Ultra-wide-field angiography findings in acute Vogt-Koyanagi-Harada disease. Issue 7 (12th August 2018) - Kim, Patrick; Sun, Hae Jung; Ham, Don-Il
Abstract : Background/aims: To investigate the prevalence of abnormal central and peripheral ultra-wide-field (UWF) angiography findings, and their association with clinical features in acute Vogt-Koyanagi-Harada (VKH) disease. Methods: This retrospective, observational study included 26 eyes of 13 treatment-naïve patients with acute VKH disease who underwent UWF fluorescein angiography (FA). Sixteen eyes of eight patients also underwent UWF indocyanine green angiography (ICGA). A circle simulating the central 75° field was used to divide the acquired image into the central fundus area (CFA) and peripheral fundus area (PFA), in which the presence of six previously reported abnormal angiographic findings were analysed. Correlations between abnormal angiography findings in FA and clinical features were also investigated. Results: All eyes demonstrated more than one abnormal angiographic finding in both the CFA and PFA. UWF FA revealed three abnormal findings in the CFA versus the PFA: focal leakage (92.3% vs 76.9%); pooling with a dark rim (84.6% vs 53.8%); and retinal vascular leakage (0% vs 46.2%). UWF ICGA revealed three abnormal findings in the CFA versus the PFA: hypofluorescent dark dots (100% vs 100%); diffusely leaking fuzzy choroidal vessels (93.8% vs 75.0%); and late hypofluorescent patches (81.3% vs 31.3%). Pooling with a dark rim and retinal vascular leakage in the PFA were significantly associated with low initial visual acuity (p=0.03) and subfoveal choroidal thickness change ratio (p=0.04), respectively. Conclusion: Abnormal UWF angiography findings were frequently detected in the CFA and PFA. Such findings may be useful in evaluation and monitoring of VKH disease.